Pengaruh Myofacial Release Dan Stretching Terhadap Penurunan Spastisitas Otot Gastrocnemius Pada Cerebral Palsy Diplegi - Sukmana, Resza Aji, Edy Waspada, S. Fis., M. Kes (2017)
Myofacial release and stretching was manual therapy technique directed against the soft tissue of abnormal muscle tone with a rigid fascia to fixed the range of motion (ROM), decreased pain, and improved functioning of the network. The purpose of this study was to determined the effectiveness of myofacial release and stretching of the gastrocnemius muscle spasticity in cerebral palsy diplegy. Research experiment used 7 samples by measuring pre and post test in the one control group in PNTC Karanganyar. Data were analyzed used wilcoxon sign rank test to determined the effectiveness of an experiment. Interpretation resulting data can be received if the p value less than 0,05. Based on the research result of the statistical calculations amounted 0,043, wich means there was significant myofacial release and stretching to the decreased of the gastrocnemius muscle spasticity in cerebral palsy dilpegy.